Systems engineering tools and methods - Kamrani, Ali K.; Azimi, Maryam (Boca Raton : CRC Press, 2011)
'Waste, inadequate system performance, cost overruns, and schedule problems often result from failure to apply advanced systems engineering early in project development. Systems engineering is a systematic method to manage the formulation, analysis, and interpretation of what a system will produce and whether the outcome is the one that is desired. This book provides detailed discussions on engineering design and management processes within system lifecycles. The text addresses various issues of systems engineering fundamentals, emphasizing an integrated approach. The author presents methods, frameworks, techniques, and tools for designing, implementing, and managing large-scale systems'--
Includes bibliographical references and index.
Keywords: Systems engineering; Project management